Vertical integration to avoid contracting with potential competitors: Evidence from bankers' banks - Brickley, James A.; Linck, James S.; Smith, Clifford W. (Journal of Financial Economics, 2012)
We examine a vertical integration decision within the commercial banking industry. During the last quarter of the 20th century, some community banks reduced their traditional reliance on correspondent banks for upstream products and services by joining bankers' banks, a form of business cooperative. Research on vertical integration focuses primarily on firm-specific investment, market power, and government regulation. However, this case is difficult to explain in terms of these standard vertical integration motives. Our evidence suggests that bankers' banks are a response to technological change and deregulation that results in increased costs faced by community banks in dealing with correspondent banks as both suppliers and potential competitors. For instance, loan participations require sharing proprietary information about major loan customers, something a community bank would not want to provide to a potential competitor.